2004
DOI: 10.1029/2004wr003279
|View full text |Cite
|
Sign up to set email alerts
|

Estimating accumulation rates and physical properties of sediment behind a dam: Englebright Lake, Yuba River, northern California

Abstract: [1] Studies of reservoir sedimentation are vital to understanding scientific and management issues related to watershed sediment budgets, depositional processes, reservoir operations, and dam decommissioning. Here we quantify the mass, organic content, and grain-size distribution of a reservoir deposit in northern California by two methods of extrapolating measurements of sediment physical properties from cores to the entire volume of impounded material. Englebright Dam, completed in 1940, is located on the Yu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 35 publications
3
59
0
3
Order By: Relevance
“…Its primary purpose was to contain sediment from anticipated future hydraulic mining. Hydraulic mining resumed for a brief period after completion of the dam (James, submitted for publication); however by May 2001 Englebright Lake had accumulated 21.9 million m 3 of sediment (Childs et al, 2003;Snyder et al, 2004). One of the primary goals of this paper is to identify major sediment sources in the upper Yuba River and the reservoir sediment volume is an ideal gauge that suggests the relative magnitude of sediment deliveries integrated over the past 62 years.…”
Section: Discussionmentioning
confidence: 99%
“…Its primary purpose was to contain sediment from anticipated future hydraulic mining. Hydraulic mining resumed for a brief period after completion of the dam (James, submitted for publication); however by May 2001 Englebright Lake had accumulated 21.9 million m 3 of sediment (Childs et al, 2003;Snyder et al, 2004). One of the primary goals of this paper is to identify major sediment sources in the upper Yuba River and the reservoir sediment volume is an ideal gauge that suggests the relative magnitude of sediment deliveries integrated over the past 62 years.…”
Section: Discussionmentioning
confidence: 99%
“…The lower Yuba River flows from Englebright Dam, through the Yuba Gold Fields over Daguerre Point Dam, to the Feather River at Marysville (Figure 2). Englebright Dam traps most sediment leaving the mountains and has arrested the delivery of reworked hydraulic mining sediment to the Valley since it was constructed in 1941 [15,20,21]. Most sediment transport in the lower Yuba River is produced from mining sediment stored downstream of Englebright, where the valley is wider, gradients decrease and much HMS was deposited.…”
Section: Background and Study Areamentioning
confidence: 99%
“…This is especially true in California where 60 percent of the water comes from the Sierra Nevada and most of the major river systems contain dams where storage area can be greatly reduced by accumulating sediment [19]. Several case studies on California reservoirs have shown that the fine sediment fraction (silt, clay, and sand), which can cause turbidity in headwater reaches, accounts for the majority of accumulated sediment in reservoirs [20,21]. Sediment and sediment transport also play a key role in nutrient cycling, aquatic-habitat quality, flood-control and water-supply infrastructure, and contaminant transport [22].…”
Section: Introductionmentioning
confidence: 99%